(3GdQbjI GdTQYjIs - (3NGdO, NGdO CMeOs ((3GdLjRI, eUQs (3OGQ GdaGQhbs, 2010)
(3YGde JJdGWe GdCehGL ajg, jHMK cd EfSGf Yf Whb fLGI jeSc Hg hjdLC Edjg dYdg jfLh aj gPG GdHMQ GdeJdGWe GdPj ZWJ Ydjg SMH GdLgd hGdMbO hGdEdMGO(B. (3dbO CNHQfG GdQShd (B( (3Yf gPG GdReGf hhUag HCOb hUa hCLed JTHjg abGd(B: "(3jCJj Ydi GdfGS ReGf GdUGHQ ajge Ydi Ojfg cGdbGHV Ydi GdLeQ(B" (3QhGg GdJQePj(B. (3CeG hbO XgQJ GdOYhGJ ef cd MOH hUhH JOYh Edi GdMVGQI hGdeOfjI hQaV cd eG gh bOje(B- (3hdh cGf OjfG hYbjOI(B- (3HMLI GdEUdGM hGdJbOe(B. (3aEf OGQ GdaGQhb JbOe ddbGQF gPG GdcJGH dYdg jchf Whb fLGI def VdJ Hge GdSHd, hCYjJge GdMjdI hde jLOhG ef jdLChf Edjg dJTaj UOhQge hCHOGfge(B. (3eUOGbG dbhd GdQShd GdcQje(B: "(3JQcJ ajce CeQjf df JVdhG eG JeScJe HgeG cJGH Gddg hSfI fHjg(B" (3QhGg eGdc aj GdehWCs
7 8 9 11 13 14
Keywords: (3GdCOYjI h GdChQGOs; (3GdMSOs; (3GdSMQs; (3GdSeYjGJs